2023
DOI: 10.1002/adsu.202300095
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Semiconductor Photocatalyst Nanomaterials for Energy and Environmental Applications: Fundamentals, Designing, and Prospects

Abstract: The degradation of fossil fuel and worse environmental conditions leads to the emergence of hybrid semiconductor (SC) nanomaterials as photocatalysts. Hybrid SCs have interesting physical, mechanical, optical, chemical, and electronic characteristics. Due to these properties’ absorption of light and transfer of charge takes place frequently and hence act as multifunctional surface. These materials should be attributed to their optical and electrical properties and act as multifunctional surfaces in energy prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 248 publications
0
8
0
Order By: Relevance
“…Advanced porous materials have been designed, synthesized with specific structures, and investigated in different scientific fields . The advancement of porous material ranges from traditional inorganic materials (like silica, activated carbon, and zeolites) to organic–inorganic hybrid materials (like metal–organic frameworks (MOFs) and coordination polymers). Among these porous materials, MOFs are produced via the self-assembly of metal ions and organic ligands through coordination linkages.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced porous materials have been designed, synthesized with specific structures, and investigated in different scientific fields . The advancement of porous material ranges from traditional inorganic materials (like silica, activated carbon, and zeolites) to organic–inorganic hybrid materials (like metal–organic frameworks (MOFs) and coordination polymers). Among these porous materials, MOFs are produced via the self-assembly of metal ions and organic ligands through coordination linkages.…”
Section: Introductionmentioning
confidence: 99%
“…3.2 eV for TiO 2 , ZnO, and Nb 2 O 5 ), leading to limited utility for photosynthesis and photodegradations. According to the literature, one of the effective methods to improve their activity under visible light irradiation and achieve this goal is to design more complex catalytic systems and construct heterojunction containing plasmonic metals, in order to broaden the absorption spectrum as well as to improve the carrier separation efficiency ( Leong et al, 2018 ; Prakash et al, 2018 ; Yang et al, 2021b ; Gao et al, 2022 ; Liu et al, 2022 ; Ly et al, 2023 ; Mishra et al, 2023 ). Up to now, many researchers have reported that these large band gap semiconductors combined with noble metal nanoparticles (such as Au, Ag, etc .)…”
Section: Introductionmentioning
confidence: 99%
“…For environmental applications inorganic oxides can be used. [24][25][26] Manganese oxides [27] can be used for environmental applications due to their low toxicity, low cost, narrow bandgap, multiple valences of manganese (Mn 2 + , Mn 3 + , and Mn 4 + ). Various methods are currently used for the synthesis of manganese-based micro/nanomotors, such as chemical coprecipitation, porous template-assisted synthesis, hydrothermal and microfluidic methods.…”
Section: Introductionmentioning
confidence: 99%